GOULD'S TURKEY SURVIVAL AND HABITAT SELECTION MODELING IN SOUTHEASTERN ARIZONA - Brian F. Wakeling; Susan R. Boe; MariAnn M. Koloszar; Timothy D. Rogers (Wildlife Society Bulletin)
Abstract: We studied survival, home range size, and habitat selection between a stable population of Gould's turkey (Meleagris gallopavo mexicana) in the Huachuca Mountains and a recently translocated population of Gould's turkey with limited reproductive success in the Galiuro Mountains of southeastern Arizona between January 1998 and October 1999. Survival and home range size were similar for both turkey populations. In the Huachuca Mountains, grassland and pine (Pinus spp.) vegetation associations positively influenced habitat occupation, whereas mesquite (Prosopis velutina) vegetation association, bare ground, and proximity to springs negatively influenced habitat occupation. Shrubland and pine vegetation associations and greater elevation positively influenced habitat occupation in the Galiuro Mountains, whereas proximity to stream courses and roads negatively influenced habitat occupation. Generally, both populations used similar habitats, although habitat models for the 2 mountain ranges reflected differences in the availability of vegetation associations. We conclude that both mountain ranges contain suitable habitat for Gould's turkeys, although in differing amounts and arrangements. We believe that the limited reproductive success in the Galiuro Mountains results from high initial adult mortality due to habitat unfamiliarity immediately following translocation, limited range of suitable turkey habitat, small breeding population size resulting from initial high mortality, and the greater effect of stochastic variation in climate and predation on small populations. We recommend that our habitat models be used to evaluate and prioritize future Gould's turkey release sites in the Southwest within the range of habitat attributes we measured.